XRD investigation of the effect of MgO additives on ZTA-TiO2 ceramic composites - Ahmad Azhar, Ahmad Zahirani; Manshor, Hanisah; Mohd Ali, Afifah (Institute of Physics Publishing, 2018)
Alumina (Al2O3) based ceramics possess good mechanical properties and suitable for the application of cutting inserts. However, this monolithic ceramics suffer from lack of toughness. Hence, there are some modification were made such as the addition of yttria stabilized zirconia (YSZ) to the Al2O3 helps in increasing the toughness of the Al2O3 ceramics. Some additives such as MgO and TiO2 were used to further improve the mechanical properties of ZTA. In this study, high purity raw materials which consist of ZTA-TiO2 were mixed with different amount of MgO (0.0 – 1.0 wt %). The mixture of materials was going through wet mixing, compaction and pressureless sintering at 1600°C for one hour. The samples were characterized for phase analysis, microstructure, shrinkage rate, bulk density, Vickers hardness and fracture toughness. Based on the XRD analysis results, the secondary phase (MgAl2O4) was detected in the sample with 0.5 wt% of MgO onwards which leads to grains refinement, thus improve the density and hardness of ZTA-TiO2-MgO ceramics composites.